Multilingualism and Bilingualism - Sammy Chumbow, Beban (IntechOpen, 2018)
Research in the area of bilingualism and multilingualism invariably produces fascinating insights. In the Europe of yesteryears, the paradigm of one nation one language was dominant and fashionable as a nation-building ideology that multilingualism was considered a curse, a demon that had to be exorcised. Today, the avalanche of empirical evidence of research findings has established multilingualism and pluralism as an ideal for national development. The nine chapters of this book provide further elucidations of the issue of benefits of bilingualism and multilingualism and also provide original research findings on developments in the areas of psychological dimensions of bilingualism and bilingualism in information retrieval systems. The book by its illuminating description and insightful analysis of issues of bilingualism will be of significant interest to scholars, researchers, and all concerned with bilingualism and multilingualism from whatever perspective.